2012
DOI: 10.1016/j.mrgentox.2011.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Single-walled carbon nanotube-induced mitotic disruption

Abstract: Carbon nanotubes were among the earliest products of nanotechnology and have many potential applications in medicine, electronics, and manufacturing. The low density, small size, and biological persistence of carbon nanotubes create challenges for exposure control and monitoring and make respiratory exposures to workers likely. We have previously shown mitotic spindle aberrations in cultured primary and immortalized human airway epithelial cells exposed to 24, 48 and 96 μg/cm 2 single-walled carbon nanotubes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
123
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(138 citation statements)
references
References 72 publications
(99 reference statements)
11
123
3
1
Order By: Relevance
“…Specifically, our study shows that after 24 h exposure, MWCNTs localize at the cell nucleus, with nanotube localization inducing changes in the nucleus mechanics by increasing its stiffness and overall Young's modulus with more than 36.6% than for control cells (either cells exposed to 1 h acids-washed MWCNTs for 1 h or to the control cells). Combining our data with previous reports that indicate that MWCNTs interact with microtubules, [22,46] the mitotic spindle, [22] DNA and cell division apparatus, [17,18] we propose now that the observed stiffness due to exposure to 1 h acids-washed MWCNTs could lead the reorganization of the three-dimensional cellular cytoskeletal network. Such reorganization could potentially disrupt the mitotic spindle, [22] inducing errors in chromosome numbers to be propagated through further cellular division [19] as characteristics of cancer cells.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Specifically, our study shows that after 24 h exposure, MWCNTs localize at the cell nucleus, with nanotube localization inducing changes in the nucleus mechanics by increasing its stiffness and overall Young's modulus with more than 36.6% than for control cells (either cells exposed to 1 h acids-washed MWCNTs for 1 h or to the control cells). Combining our data with previous reports that indicate that MWCNTs interact with microtubules, [22,46] the mitotic spindle, [22] DNA and cell division apparatus, [17,18] we propose now that the observed stiffness due to exposure to 1 h acids-washed MWCNTs could lead the reorganization of the three-dimensional cellular cytoskeletal network. Such reorganization could potentially disrupt the mitotic spindle, [22] inducing errors in chromosome numbers to be propagated through further cellular division [19] as characteristics of cancer cells.…”
supporting
confidence: 87%
“…[16,17] Recent work has shown that in vitro and in vivo exposure to SWCNTs can lead to alterations in DNA structure. [18,19] For instance, our recent studies have shown that 24 to 72 h exposure of epithelial cells to SWCNTs induced centrosome fragmentation and aneuploidy [18,20] similar to the genotoxin vanadium pentoxide. [21] Likewise, cellular exposure to MWCNT disrupted the mitotic spindle by association with microtubules, [22] induced polyploidy [17] and changes in chromosome number in a fashion similar to crocidolite asbestos.…”
mentioning
confidence: 99%
“…Sargent et al (28) provided evidence of SWCNT interference with the mitotic spindle in human airway epithelial cells leading to induction of aneuploidy, an early event in the progression of many cancers. Notably, significant disruption of the mitotic spindle by SWCNTs was detected at occupationally relevant doses (29). The CNT bundles are similar to the size of microtubules that form the mitotic spindle and this "bio-mimicry" may explain how these nanomaterials are incorporated into the mitotic spindle apparatus.…”
Section: Towards a Molecular Nanotoxicologymentioning
confidence: 92%
“…Stwierdzono, że SWCNT i MWCNT: Baytubes® oraz Nanotec (średnica 10-30 nm), nie wykazywały działania genotoksycznego (aberracji chromosomowych i zwiększenia częstości wymiany chromatyd siostrzanych) w fibroblastach chomika chińskiego lub ludzkich limfocytach [37,38]. W ludzkich komórkach nabłonka oddechowego eksponowanych na SWCNT zaobserwowano zaburzenia podziałów mitotycznych [43].…”
Section: Droga Dermalnaunclassified